Development of a serious game for learning about safe sex and contraception in adolescence - Lilian Mayumi Chinen Tamashiro; Luciana Mara Monti Fonseca (Universidade de São Paulo, 2024)
Objectives: to develop a serious game in a mobile application for learning about safe sex and contraception with the active participation of adolescents; and evaluate the content, appearance and usability of the technology with adolescents and experts. Method: this is an applied research project into the development of a serious game, carried out in two stages: development of the technology itself; and evaluation of the content, appearance and usability of the application. Teenagers from a public school in the city of São Paulo-Brazil took part in the technology development stage. The evaluation was carried out by the adolescents and experts in the areas of public health and health technology. The following criteria were used: educational aspects, environment interface and didactic resources. Results: Prinventon App ® was developed, a serious game set in a virtual city, designed to address adolescent sexuality. The app received 90% positive responses and had a Content Validity Index of 0.80, which was considered adequate. The suggestions and notes were accepted and implemented. The serious game was considered interesting and important in terms of the subject matter. Conclusion: it was found that the technology developed can help adolescents learn about safe sex and contraception, by addressing sexuality in adolescence in a playful and realistic way.